2013
DOI: 10.1111/bjh.12274
|View full text |Cite
|
Sign up to set email alerts
|

The clinical benefit of ruxolitinib across patient subgroups: analysis of a placebo‐controlled, Phase III study in patients with myelofibrosis

Abstract: Summary Myelofibrosis (MF) patients can present with a wide spectrum of disease characteristics. We analysed the consistency of ruxolitinib efficacy across patient subgroups in the COntrolled MyeloFibrosis Study With ORal JAK Inhibitor Treatment (COMFORT-I,) a double-blind trial, where patients with intermediate-2 or high-risk MF were randomized to twice-daily oral ruxolitinib (n = 155) or placebo (n = 154). Subgroups analysed included MF subtype (primary, post-polycythaemia vera, post-essential thrombocythaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 21 publications
1
64
0
4
Order By: Relevance
“…9,10 There was no trend among the causes of death between men and women to account for the difference in survival observed; it is likely a composite of multiple factors that these studies were not specifically designed to evaluate. Although the above factors were shown to be prognostic in this analysis, a post hoc subgroup analysis of COMFORT-I 26 and a similar analysis of COMFORT-II 27 demonstrated that ruxolitinib treatment benefited each subgroup compared with placebo and BAT separately.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 60%
“…9,10 There was no trend among the causes of death between men and women to account for the difference in survival observed; it is likely a composite of multiple factors that these studies were not specifically designed to evaluate. Although the above factors were shown to be prognostic in this analysis, a post hoc subgroup analysis of COMFORT-I 26 and a similar analysis of COMFORT-II 27 demonstrated that ruxolitinib treatment benefited each subgroup compared with placebo and BAT separately.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 60%
“…While this is likely appropriate in terms of therapeutic management, as supported also by the comparable efficacy of JAK2 inhibitors in subgroup analysis of patients treated with ruxolitinib [4,5] fedratinib [6], and pacritinib [7], it remains to be fully addressed whether the clinical course of secondary MF differs from PMF and which are the variables eventually influencing it. In particular as regards prognosis, there are evidences that the International Prognostic Score System (IPSS), that is routinely employed for both PMF and secondary MF, may not be performing satisfactorily in secondary forms of MF [8].…”
Section: Introductionmentioning
confidence: 99%
“…24 Long-term follow-up of COMFORT-1 patients recently presented by Verstovsek et al 25 continues to demonstrate an OS benefit in favor of ruxolitinib therapy after an additional year of observation (HR 5 0.58; 95% CI: 0.36, 0.95; P 5 .028) (Figure 1). This difference remained statistically significant across all MF subgroups, starting drug doses, baseline risk status, and hemoglobin level.…”
Section: Ruxolitinib Survival Benefit In Myelofibrosis 4833mentioning
confidence: 85%
“…19 A planned additional data cutoff was also conducted after an additional 4-month followup period. At a median follow-up of 52 and 51 weeks, 13 (8.4%) BLOOD, 13 JUNE 2013 x VOLUME 121, NUMBER 24 …”
Section: Prospective Studiesmentioning
confidence: 99%